Definition of oriR, the minimum DNA segment essential for initiation of R1 plasmid replication in vitro. - Masai, H (1983)
The 3.6-kilobase Bgl II-EcoRI fragment from R1 plasmid containing copA, repA, and the replication origin (ori) was inserted into the ColE1-type plasmid pUC8. The resulting hybrid plasmid replicates in extracts prepared from both polA- and polA+ cells, whereas pUC8 replicates only in a polA+ extract. This characteristic provides a method for assaying the repA and ori functions. Hybrid plasmids that were either repA- or ori- were unable to replicate in a polA- cell extract. Replication of the repA- ori+ plasmid was restored by complementation of the repA defect by a repA+ ori- plasmid in vitro. Successful complementation of the repA function in vitro provides a method for assaying the repA protein. In order to define the minimum DNA segment with origin function (oriR), deletions were introduced starting from either side of the insert, and the replication properties of the plasmids carrying these deletions were examined in a polA- cell extract. The right end of oriR was located at position 1,611 in the nucleotide coordinates defined previously [Ryder, T., Rosen, J., Armstrong, K., Davidson, D. & Ohtsubo, E. (1981) in The Initiation of DNA Replication: ICN-UCLA Symposia on Molecular and Cellular Biology, ed. Ray, D.S. (Academic, New York), Vol. 22, 91-111]. By complementing repA- ori+ plasmids with the repA+ ori- plasmid, the left end of oriR was localized at position 1,424. Therefore, the oriR sequence, localized within a region of 188 base pairs, is separate from the repA gene. A hybrid plasmid carrying the 206-base-pair segment between positions 1,406 and 1,611 also replicates in a polA- cell extract when the repA function is supplied in trans. Removal of an additional 66 base pairs (positions 1,406-1,471) inactivates the function of the minimal oriR segment.